STRATEGIC DIRECTIONS OF PIG BREEDING DEVELOPMENT IN UKRAINE (INNOVATIVE ECONOMY, 2021)
Samoilyk Yu.V., Lavruk V.V., Ibatullin M.I. STRATEGIC DIRECTIONS OF PIG BREEDING DEVELOPMENT IN UKRAINEPurpose. The aim of the article is the development of scientifically substantiated proposals for state support of pig production in Ukraine, which will meet the needs of the domestic market and increase exports.Methodology of research. During the research, general scientific and special methods of economic research were used, in particular: system approach - in studying the connections between phenomena and processes in the system of ensuring the effective development of pig breeding; grouping - to determine the impact of various factors on the level of efficiency of pig production and its quality; comparative - to compare economic processes in pork production in different time periods in order to identify the cause-and-effect relationship; dialectical, abstract and logical - in the implementation of theoretical generalizations, the formation of conclusions. The calculation and constructive method was used in determining the strategic priorities for the development of pig production in agricultural enterprises, substantiation of instruments of state support for pig production.Findings. It is established that the strategic priority of pig production is the introduction of environmentally friendly resource-saving technologies for keeping and feeding pigs, intensive use of the breeding herd and new biotechnological techniques to improve the viability of piglets, energy saving and energy efficiency programs, farm biosafety.Originality. Methodological approaches to substantiation of assessment of potential opportunities of agricultural enterprises in improving the efficiency of pig production and, accordingly, strengthening their market position by calculating an integrated indicator, which includes: market share in the structure of sales, production and livestock, cost indices, profitability, prices, specialization, productivity of pigs, on the basis of which the following groups are distinguished: leaders, enterprises with a strong competitive position, with a weak competitive position, outsiders.Practical value. The results of grouping enterprises on the basis of the calculation of the integrated indicator can be the basis for making management decisions to improve the efficiency of enterprises as a whole. Thus, agricultural enterprises producing pig products with a weak competitive position can increase production efficiency and strengthen their position, provided appropriate technological modernization of the production process, attracting investment in creating their own processing facilities and branded trade, development of organic pigs, as well as integration with meat processing enterprises, trade establishments.Achieving effective pig farming in outsider agricultural enterprises is possible under the condition of technical re-equipment of the production process on an innovative basis, reduction of the cost level due to internal reserves, exit from business; merger with a more powerful competitor.Key words: pig breeding, state support, integrated assessment, agricultural enterprise, competitiveness.
Keywords: Key words; pig breeding; state support; integrated assessment; agricultural enterprise; competitiveness.